2009
DOI: 10.1007/s10658-009-9518-z
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco ringspot virus persists in the shoot apical meristem but not in the root apical meristem of infected tobacco

Abstract: We analysed the kinetics of virus distribution in Tobacco ringspot virus (TRSV)-infected tobacco. Infected plants developed asymptomatic leaves above the symptomatic leaves that exhibited ringspots. We detected virus in the shoot apical meristem (SAM). Time-course immunohistochemical microscopy showed that TRSV continuously distributed in the centres of the SAM and in leaf primordia. In contrast, TRSV infection was transient in the root meristem. In western blot and RT-PCR analyses, TRSV infection occurred onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Therefore, we hypothesize that similarly to TRSV [10] , entry of AILV-V in the meristematic tissues was permitted by the very low concentration of viral RNA or virus particles at a time of infection that would be insufficient to trigger an RS-mediated response. Results of immunolocalization between 7 and 28 dpi showed a higher concentration of virus in meristem than in surrounding tissues, as with TRV and TRSV [16] , [19] , suggesting poor or no AILV-V replication and movement in the SAM. The successive reduction of virus titer observed in SAM by 40 dpi might be due to hindered viral transport into the meristem as a consequence of virus clearance in tissues of mature leaves.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, we hypothesize that similarly to TRSV [10] , entry of AILV-V in the meristematic tissues was permitted by the very low concentration of viral RNA or virus particles at a time of infection that would be insufficient to trigger an RS-mediated response. Results of immunolocalization between 7 and 28 dpi showed a higher concentration of virus in meristem than in surrounding tissues, as with TRV and TRSV [16] , [19] , suggesting poor or no AILV-V replication and movement in the SAM. The successive reduction of virus titer observed in SAM by 40 dpi might be due to hindered viral transport into the meristem as a consequence of virus clearance in tissues of mature leaves.…”
Section: Discussionmentioning
confidence: 96%
“…The first studies linking recovery of plants from viral infection with RS were carried out on nepoviruses [15] , but only few of them have addressed viral distribution in SAM in the context of recovery. Dong et al [19] studied dynamics of Tobacco ringspot virus (TRSV) distribution in the SAM and in the root apical meristem of tobacco, coming to the conclusion that TRSV persisted in the SAM of tobacco and the asymptomatic leaves of Nicotiana benthamiana , but it was transient in the root apical meristem and asymptomatic leaves of tobacco plants. Siddiqui et al [10] reported that transgenic expression of some VSR affected the temperature-dependent infection pattern of the TRSV potato calico strain but no information was provided on the effect of such VSR on the recovery phenotype of TRSV-infected tobacco plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental evidence is still insufficient because hypotheses have not been fully tested yet. There are published records of viruses and viroids capable of invading meristems in some species (Agüero et al, 2013;Dong et al, 2010;Martín-Hernández & Baulcombe, 2008;Mochizuki & Ohki, 2015;Rubies-Autonell & Faccioli, 1985;Toussaint et al, 1984;Walkey & Webb, 1968;Zhang et al, 2015). One example is potato virus X (Appiano & Pennazio, 1972), a potexvirus like CsCMV.…”
Section: Evidence Of Cassava Common Mosaic Virus In Cassava Shoot Api...mentioning
confidence: 99%